Way up and over everything - McGill, Alice; Daly, Jude (Boston : Houghton Mifflin, 2008)
In this retelling of a folktale, five Africans escape the horrors of slavery by simply disappearing into thin air.
Booklist.
4.3
3-6
Keywords: African Americans -- Folklore; Folklore -- United States; Slavery -- Folklore; African Americans -- Folklore; Folklore; Slavery -- Folklore; African Americans -- Folklore; Folklore -- United States; Slavery -- Folklore